Prevalence and Intensity of Hookworm Infections in Ekiti, Nigeria; A Cross Sectional Study in State Specialist Hospital and Federal Medical Centre - Adewole, SO; Akingbolu, IA (Bangladesh Journal of Scientific and Industrial Research, 2010)
Prevalence of hookworm and other helminthes infections from year 2004 till May, 2007 was carried out in both the State Specialist Hospital and Federal Medical Centre, in Ekiti State. Of the 2,686 recorded and examined, 1,246 persons representing 46.3% were infected with helminthes while 53.7% were infected with other helminthes like Ascaris lumbricoides and Trichuris trichura. At State Specialist Hospital (Ado-Ekiti), 646 persons representing 47.1% were infected with hookworm while 600 persons representing 45.5% were infected with hookworm at Federal Medical Centre, (Ido-Ekiti). There is a significant difference (X2=8.9; P< 0.05) in the prevalence and susceptibility of males and females to infections in the State Specialist hospital, Ado-Ekiti. Also, there is no significant difference (X2=3.82; P > 0.05) in the prevalence and susceptibility of males and females to hookworm infections. Key words: Prevalence; Epidemiology; Helminthes; Infections Hospital. DOI: 10.3329/bjsir.v44i4.4588 Bangladesh J. Sci. Ind. Res. 44(4), 399-402, 2009